Implementasi Pendidikan Inklusi pada Pembelajaran Membaca Permulaan bagi Siswa Slow Learner Kelas 1 SDN Sukamanah - Siti Humaeroh; Enggar Utari (Varied Knowledge Journal, 2026)
This study aims to analyze the implementation of inclusive education in improving early reading skills for slow learner students in the first grade of SDN Sukamanah. The research is driven by the heterogeneity of literacy skills, where 5 students (19%) out of 26 total students are categorized as slow learners, characterized by short-term memory impairments and difficulty in visually distinguishing similar letter symbols. A qualitative case study method was employed, with data collection through participant observation, documentation, and oral cognitive tests. Intervention strategies included differentiated instruction in content, process, and learning environment, the use of interactive media such as Interactive Flat Panels (IFP) and individualized scaffolding. The results indicated that 20 students (77%) achieved reading independence. Specifically, the slow learner group showed an average score increase of 30.80%, rising from an initial 34.67% (Needs Guidance category) to 65.47% (Fair category). These findings prove that the integration of differentiation strategies and multisensory stimulation through interactive technology effectively bridges cognitive barriers, providing equitable learning opportunities within an inclusive education setting.